2020
DOI: 10.3390/cancers12082137
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Targeting of Mcl-1 Is Synthetically Lethal with Bcl-xL/Bcl-2 Inhibition in Model Systems of Glioblastoma

Abstract: Apoptotic resistance remains a hallmark of glioblastoma (GBM), the most common primary brain tumor in adults, and a better understanding of this process may result in more efficient treatments. By utilizing chromatin immunoprecipitation with next-generation sequencing (CHIP-seq), we discovered that GBMs harbor a super enhancer around the Mcl-1 locus, a gene that has been known to confer cell death resistance in GBM. We utilized THZ1, a known super-enhancer blocker, and BH3-mimetics, including ABT263, WEHI-539,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…Then, the mechanistical assay validated that the SE‐mediated H3K27ac modification is responsible for the downregulation of SLC30A3 in GBM. The similar mechanism of action has also been reported in a recent report where GBM harbors a SE around the Mcl‐1 locus, and THZ1, a SE blocker, elicited an impairment of the Mcl‐1 enhancer region, resulting in an inhibition of Mcl‐1 transcript and protein levels 22 …”
Section: Discussionsupporting
confidence: 80%
“…Then, the mechanistical assay validated that the SE‐mediated H3K27ac modification is responsible for the downregulation of SLC30A3 in GBM. The similar mechanism of action has also been reported in a recent report where GBM harbors a SE around the Mcl‐1 locus, and THZ1, a SE blocker, elicited an impairment of the Mcl‐1 enhancer region, resulting in an inhibition of Mcl‐1 transcript and protein levels 22 …”
Section: Discussionsupporting
confidence: 80%
“…Apoptosis is a self-destructive process of cell stress, resulting in cell death and reduced cell viability, especially in tumor cells. Some biomarkers are used to monitor the process of apoptosis, including caspases (23), mitochondrial potential (24), and sub G1 group (25). Studies have shown that the main internal and external causes of apoptosis are related to caspases, including caspase-3 and/or caspase-9 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the anti-apoptotic Bcl-2 family member myeloid cell leukemia factor-1 (Mcl-1), which interferes in early cascade events by suppressing cytochrome c release from mitochondria, is highly expressed in human glioblastoma (Michels et al, 2005;Karpel-Massler et al, 2017). High levels of Mcl-1 mediate BH3-mimetic resistance, suggesting that a dual inactivation of Bcl-2/Bcl-xL and Mcl-1 is necessary for apoptosis of glioblastoma cells (Kouri et al, 2012;Karpel-Massler et al, 2017;Shang et al, 2020). AT-101, a small molecule targeting Mcl-1, is presently being examined in a clinical trial (Xiang et al, 2018).…”
Section: Glioblastoma Cells Are Resistant To Apoptosismentioning
confidence: 99%
“…Although inhibition of Mcl-1 has received certain attention as a potential drug target, only slowly implemented in clinical applications and poses challenges in glioblastoma treatment due to high molecular weight and the blood brain barrier. With the aim to overcome such drawbacks the use of combinatory approaches is further explored (Tron et al, 2018;Shang et al, 2020).…”
Section: Glioblastoma Cells Are Resistant To Apoptosismentioning
confidence: 99%